Continuous‐time formulations for the optimal planning of multiple refracture treatments in a shale gas well. Issue 5 (3rd February 2018) - Cafaro, Diego C.; Drouven, Markus G.; Grossmann, Ignacio E.
Significance: This work presents a continuous‐time optimization model for planning multiple refracture treatments over the lifespan of a shale gas well. We demonstrate that continuous‐time models can handle multiple restimulations very efficiently, increasing the net present value of the well development and refracturing plan. Well productivity is represented by a piecewise hyperbolic function, which accounts for when and how often the well has been refractured. We illustrate the application and effectiveness of the proposed approach for both the maximization of the total gas recovered and the maximization of the net present value. © 2018 American Institute of Chemical Engineers AIChE J, 64: 1511–1516, 2018